2002
DOI: 10.1046/j.1537-2995.2002.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between tick bites and the seroprevalence of Babesia microti and Anaplasma phagocytophila (previously Ehrlichia sp.) in blood donors

Abstract: Blood donors seropositive for B. microti and A. phagocytophila are present in Connecticut and Wisconsin. Donors readily recall previous tick bites, but self-reported bites are not reliable indicators of serologic status. The exposure of blood donors to tick-borne pathogens does suggest a need to better understand the transfusion transmission potential of these agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 39 publications
4
59
0
2
Order By: Relevance
“…in the general population, and determinations of prevalence in blood donors are rare, except for a few studies from the United States and Europe focused mostly on B. microti. In the Northeast United States, the seroprevalence of B. microti has been reported to range from 0.3% in Connecticut to 9.5% in Lyme disease patients (n ϭ 735) at the University of Connecticut (29,52,74,77,85). Several reports of B. microti in blood donors have reported rates as high as 4.3% (5 of 115 positive by IFA test) on Shelter Island, NY, an area where the parasite is highly endemic (77,80,100).…”
Section: Seroprevalencementioning
confidence: 99%
See 1 more Smart Citation
“…in the general population, and determinations of prevalence in blood donors are rare, except for a few studies from the United States and Europe focused mostly on B. microti. In the Northeast United States, the seroprevalence of B. microti has been reported to range from 0.3% in Connecticut to 9.5% in Lyme disease patients (n ϭ 735) at the University of Connecticut (29,52,74,77,85). Several reports of B. microti in blood donors have reported rates as high as 4.3% (5 of 115 positive by IFA test) on Shelter Island, NY, an area where the parasite is highly endemic (77,80,100).…”
Section: Seroprevalencementioning
confidence: 99%
“…In the Northeast United States, the seroprevalence of B. microti has been reported to range from 0.3% in Connecticut to 9.5% in Lyme disease patients (n ϭ 735) at the University of Connecticut (29,52,74,77,85). Several reports of B. microti in blood donors have reported rates as high as 4.3% (5 of 115 positive by IFA test) on Shelter Island, NY, an area where the parasite is highly endemic (77,80,100). A recent, ongoing Connecticut study reported that 1.1% of 21,523 donors tested from 2000 to 2007 were positive for B. microti antibodies by IFA testing (62).…”
Section: Seroprevalencementioning
confidence: 99%
“…Thus, Walder and co-workers in Austria chose a cut off of 1:128, the 98 th percentile of a control population with low likelihood of having had HGA [25]. (cut-off ≥64) [27], and 9.0% (32/357) in Tyrol, Austria (cut-off ≥128) [25]. In Denmark,…”
Section: Anaplasma Phagocytophilummentioning
confidence: 99%
“…31 A seroprevalence study of 992 blood-donors from Connecticut and Wisconsin demonstrated that 0.4 to 0.9% of the blood donors have A. phagocytophilum antibodies. 32 There is no U.S. mandate to screen blood products for A. phagocytophilum infection, and at least 8 cases of HGA acquired via transfusions of infected leuko-reduced blood products have been reported since 2007. 33 Beyond A. phagocytophilum, Ixodes ticks are often coinfected with other human pathogens.…”
Section: Patient Historymentioning
confidence: 99%